Utilization of Ketinting Engine Assistance and Socio-Economic Changes among Traditional Fishermen - Hannin Pradita Nur Soulthoni; Muammar Akbar Al Qhuraissy (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
Traditional fishermen in coastal Indonesia continue to face persistent productivity constraints due to limited access to efficient fishing technology. This study investigates the utilization of ketinting engine assistance and its contribution to productivity improvement and socio-economic change among fishermen in Torombia Village, Kulisusu District, North Buton Regency, Southeast Sulawesi. A qualitative case study design was employed. Data were collected through semi-structured in-depth interviews, participant observation, and documentation, involving village officials, representatives of the Marine and Fisheries Service, recipient fishermen, and non-recipient fishermen selected through purposive and snowball sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was ensured through source and method triangulation. The findings indicate that ketinting engine assistance improved operational efficiency, expanded access to more productive fishing grounds, and increased catch volume from 3–5 kg to more than 10 kg per day, along with better catch quality. The assistance also contributed to greater household financial stability, improved capacity to meet educational and healthcare needs, and reduced reliance on informal loans. The study concludes that appropriate technology, when supported by local institutions and social capital, can enhance the social functioning of coastal communities, although its long-term sustainability depends on continuous technical training and improved local spare-parts access.